Metabolomics approach discriminates toxicity index of pyrazinamide and its metabolic products, pyrazinoic acid and 5-hydroxy pyrazinoic acid. (April 2018) - Rawat, A; Chaturvedi, S; Singh, AK; Guleria, A; Dubey, D; Keshari, AK; Raj, V; Rai, A; Prakash, A; Kumar, U; Kumar, D; Saha, S
Pyrazinamide (PYZ)—an essential component of primary drug regimen used for the treatment and management of multidrug resistant or latent tuberculosis—is well known for its hepatoxicity. However, the mechanism of PYZ-induced hepatotoxicity is still unknown to researchers. Studies have shown that the drug is metabolized in the liver to pyrazinoic acid (PA) and 5-hydroxy pyrazinoic acid (5-OHPA) which individually may cause different degrees of hepatotoxicity. To evaluate this hypothesis, PYZ, PA, and 5-OHPA were administered to albino Wistar rats orally (respectively, at 250, 125, and 125 mg kg −1 for 28 days). Compared to normal rats, PYZ and its metabolic products decreased the weights of dosed rats and induced liver injury and a status of oxidative stress as assessed by combined histopathological and biochemical analysis. Compared to normal controls, the biochemical and morphological changes were more aberrant in PA- and 5-OHPA-dosed rats with respect to those dosed with PYZ. Finally, the serum metabolic profiles of rats dosed with PYZ, PA, and 5-OHPA were measured and compared with those of normal control rats. With respect to normal control rats, the rats dosed with PYZ and 5-OHPA showed most aberrant metabolic perturbations in their sera as compared to those dosed with PA. Altogether, the study suggests that PYZ-induced hepatotoxicity might be associated with its metabolized products, where 5-OHPA contributes to a higher degree in its overall toxicity than PA.